Utilization of Antioxidant Fagraea fragrans fruit as Phytocosmetics - Dasril Basir; Addy Rachmat; Julinar Julinar; Eliza Eliza (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The objective is to test the antioxidant activity of methanol (MeOH) extracts, ethyl acetate (EtOAc) fractions, and an isolated compound of F. fragrans (tembesu) fruitby using DPPH method respectively. Antioxidant is one of the main components of phytocosmetic beside anti-inflammatory, anticancer, and antimicrobial activities while phytocosmetics of F. fragrans fruit is the cosmetics that mainly use extracts or components derived from this fruit only, without preservatives, such as products that do not contain water, oils, dry ointments, or hydro-alcoholic solutions. As a result, The IC50 values of the MeOH extracts, EtOAc fractions, and the isolated compound were 186.5 ± 0.52 microgram/mL, 357.2 ± 0.59 microgram/mL, and 5.658 microgram/mL respectively. The MeOH extracts exhibited moderate antioxidant activity while the isolated compound exhibited strong antioxidant activity. The total flavonoid content of the MeOH extracts and EtOAc fraction was measured by a colorimetric assay, using reagents of 1 M sodium acetic and 10% aluminum chloride. The EtOAc fraction had a total flavonoid content of 4.505 mgQE/g-extract and total phenolic content of 13.732 mgGAE/g-extract while the MeOH extracts had a total flavonoid content of 9.088 mg QE/g-extract and total phenolic content of 23.34 mgGAE/g-extract respectively. Therefore, the utilization of MeOH extracts or the isolated compound of this fruit may be beneficial for developing skincare phytocosmetics and personal care products. Keywords: Phytocosmetics, antioxidant, Fagraea fragrans, tembesu fruit